STUDI PENENTUAN NILAI KALORI PADA BUAH DURIAN (Durio zibethinus) - Resky Perdana Yanti; Muh. Said L.; Ihsan Ihsan (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2014)
Research about Study of Determination Calorie Value in Durian Fruit (Durio zibethinus) has done. This study aims to determine the calorie value of all the materials used. The materials used are durian fruit. Materials will be determined calorie performed on ripe fruit or fresh fruit and fruit that have been dried under the sunlight. Determination of calorie value using two methods: the first method: determination of calorie value by Cobra3 and method II: determination of the calorie value by joule calorimeter. The higher specific heat and heat capacity accordingly calorie value would be even higher.